The link between patient safety competence and adverse event among master of nursing students: a cross-sectional mixed-methods study - Xin Zhang; Fei Wang; Qing Wang; Huaping Liu; Shih-Yu Lee (BMC, 2024)
Abstract Background Patient safety (PS) is a core competency for registered nurses. However, there is a gap between the PS competence of nursing students and their clinical experience in PS. This study explored the effect of PS competence levels on the occurrence of adverse events (AEs) among nursing master's students in China. Methods A sequential mixed methods design was used, with a purposive sample across seven colleges. A total of 327 graduate nursing students, aged 22 to 38, participated in the survey, and 15 participated in qualitative interviews. The Health Professional Education in Patient Safety Survey (H-PEPSS) assessed the students' competence levels in PS. The respondents also reported any AEs that they had been involved in over the past year. Results A total of 78 AEs occurred in the past year, with 17.7% of the participants involved 1 to 3 AEs. The most common AEs were medication administration errors (30.77%) and improper use of medical equipment/supplies (28.20%). Students acquired more competencies from the clinical setting than from the classroom setting. Three competencies learned from classroom settings were associated with clinical AEs: low clinical safety skills [OR = 0.61], inappropriate identify, response to and disclosing AE and close calls [OR = 0.454], and low confidence in working in teams with other health professionals [OR = 2.168]. Qualitative data analysis revealed five themes: recognizing AEs, reducing harm by addressing immediate risks to patients and others involved, promoting safe medication and clinical practice, managing members' authority and team dynamics, and dealing with inter-professional conflict. Conclusions The quantitative and qualitative data align, supporting the enhancement of students' PS competence.